2015
DOI: 10.1371/journal.pone.0129129
|View full text |Cite
|
Sign up to set email alerts
|

Countdown to 2015: Tracking Maternal and Child Health Intervention Targets Using Lot Quality Assurance Sampling in Bauchi State Nigeria

Abstract: BackgroundImproving maternal and child health remains a top priority in Nigeria’s Bauchi State in the northeastern region where the maternal mortality ratio (MMR) and infant mortality rate (IMR) are as high as 1540 per 100,000 live births and 78 per 1,000 live births respectively. In this study, we used the framework of the continuum of maternal and child care to evaluate the impact of interventions in Bauchi State focused on improved maternal and child health, and to ascertain progress towards the achievement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
(16 reference statements)
0
9
0
1
Order By: Relevance
“…LQAS is a small-sample alternative to traditional population-based survey methodology, which has gained increasing application in rapid turnaround public health evaluations [ 17 , 18 ]. Details of this methodology have been described elsewhere [ 19 ]. It is mostly useful in determining the program coverage status of a “supervision area” (SA) against a set target or intervention coverage.…”
Section: Methodsmentioning
confidence: 99%
“…LQAS is a small-sample alternative to traditional population-based survey methodology, which has gained increasing application in rapid turnaround public health evaluations [ 17 , 18 ]. Details of this methodology have been described elsewhere [ 19 ]. It is mostly useful in determining the program coverage status of a “supervision area” (SA) against a set target or intervention coverage.…”
Section: Methodsmentioning
confidence: 99%
“…According to available report, the maternal mortality ratio (MMR) in Bauchi is 1540 per 100 000 live births, while the infant mortality rate (IMR) is 78 per 1000 live births. 23 A total of 45 individuals took part in the workshop. Table 1 presents the profile of the attendees.…”
Section: Methodsmentioning
confidence: 99%
“…Achieving the desired coverage levels remains critical. Results of a previous study in Bauchi, a northeastern state, also used similar LQAS data and reported similar inter-LGA variations in the indicators of continuum of care although only modest improvements in these indicators were reported ( 31 ). Studies have used data from various other methodologies for similar exploration such as data from national surveys ( 32 ), a LIST model exploration ( 33 , 34 ), and a health system evaluation framework developed by Countdown In-Depth Country Case Studies ( 34 ).…”
Section: Discussionmentioning
confidence: 60%